Analisis Routing Multi Copy Dengan Stationary Relay Node Dan Management Buffer First In - First Out (FIFO) Pada Delay Tolerant Network (DTN) - Muhammad Reza Wahyu Chrisdyan; Rakhmadhany Primananda; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
On the delivery of digital data, a big delay is one of the factors in failure of the receipt of message. On this problems, one theory that can be applied is a DTN network (delay tolerant networking). DTN has advantages when its applied to network with long delay characteristics, the high degree of loss, and the low level of connectivity and minimal infrastructure. Multi Copy routing types on DTN can maximize the ratio of delivery and reduce delays but requires additional network resources. A lot of research that assumes a network resource is infinite, one of them is buffer. DTN can implement Buffer management policy as a limited buffer optimization when sending messages. Stationary Relay Node at DTN can be used this way to increase probability of the acceptance of the message as well as a bridge for sending messages. At this time, the research protocol comparing DTN routing Multi Copy by adding stationary Relay Node and Buffer management algorithm with a first in-first out were simulated using a Simulator. The test results are analyzed using the performance parameters of the probability of shipping and Overhead ratios with scenarios using epidemic routing, prophets and spray and wait by moving as many as 150 nodes and Node Relays as many as 10 Stationary, the message size of 5 MB and 30 MB of buffer limitation, 50 MB, 80 MB and 100 Mb. From the results of testing and analysis can be concluded that routing spray and wait is effective to convey the message with the network load that is lower than the other routing that applied with the greatest probability value delivery 0.2464 and Overhead ratio amounted to 10.85%.